Mardi Gras : a Cajun country celebration - Hoyt-Goldsmith, Diane (New York : Holiday House, 1995)
Introduces a Louisiana Cajun family and their celebration of Mardi Gras including the music, the food, and the costumes.
Includes index.
Keywords: Carnival -- Louisiana -- Juvenile literature; Cajuns -- Louisiana -- Social life and customs -- Juvenile literature; Mardi Gras; Cajuns; Louisiana -- Social life and customs -- Juvenile literature; Louisiana